2001
DOI: 10.1248/yakushi.121.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sho-saiko-to (Xiao Chai Hu Tang), a Chinese Traditional Medicine, on the Gastric Function and Absorption of Tolbutamide in Rats

Abstract: This study was carried out to investigate the eŠects of Sho-saiko-to (Xiao Chai Hu Tang), a Chinese traditional medicine, on the gastric function including the gastric emptying rate (GER) and intragastric pH in rats. Additionally, the eŠects of the GER and intragastric pH on tolbutamide absorption after oral administration were examined. The GER measured at 40 min after dosing was reduced to about 70% by the pretreatment of Sho-saiko-to (500 mg/kg). The plasma tolbutamide concentration in the rats treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…TJ-9 (0.125-0.5 g/kg) has been reported to have no inhibitory effects on the gastric emptying rate (GER). 19) Nishimura et al 20) however, reported that TJ-9 (0.25-0.75 g/kg) delayed gastric emptying without regard to the increase of intragastric pH and consequently could decrease gastrointestinal absorption of tolbutamide, speculating that it may be caused by [6]-gingerol, a component of Zingiberis Rhizome which is one of 7 kinds of constituents in TJ-9.…”
Section: Fig 4 Effects Of Tj-9 and Bacl 2 On Gastric Emptying In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…TJ-9 (0.125-0.5 g/kg) has been reported to have no inhibitory effects on the gastric emptying rate (GER). 19) Nishimura et al 20) however, reported that TJ-9 (0.25-0.75 g/kg) delayed gastric emptying without regard to the increase of intragastric pH and consequently could decrease gastrointestinal absorption of tolbutamide, speculating that it may be caused by [6]-gingerol, a component of Zingiberis Rhizome which is one of 7 kinds of constituents in TJ-9.…”
Section: Fig 4 Effects Of Tj-9 and Bacl 2 On Gastric Emptying In Ratsmentioning
confidence: 99%
“…21) Our results were similar to the latter findings. 20) Accordingly, it was considered that a reduced and slowed absorption of CBZ might be attributed to the decrease in gastric emptying induced by TJ-9. With CBZ-E, the concentration at all time points and the AUC 0-°w ere lower in the TJ-9 administration group than the control group.…”
Section: Fig 4 Effects Of Tj-9 and Bacl 2 On Gastric Emptying In Ratsmentioning
confidence: 99%
“…1). The inhibitory zone diameters of BBRHCl used, in our study, were compared with that of teicoplanin (mean inhibitory zone diameter 15 mm) [14] and the breakpoint correlates for the EUCAST epidemiological cutoff values of metronidazole and vancomycin (mean inhibitory zone diameters being 23,19 [mm], respectively) [13]. The diameters of zone of inhibition for BBRHCl (all the test concentrations) were significantly lesser (P≤0.0001) than the EUCAST epidemiological cutoff value for metronidazole (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the pharmaceuticals prescribed in advanced countries are compounds derived from plants or plant products [3]. Improvement in the recovery of gastrointestinal function was demonstrated in preclinical and clinical studies using TCM based therapies [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to predict and prevent serious reactions induced by drug interaction, it is necessary to characterize the mechanism for increased absorption of tolbutamide after co‐administration with Sho‐saiko‐to. In previous studies, we have shown that Sho‐saiko‐to did not affect the gastric absorption of tolbutamide in rats [11] and that dissolution of tolbutamide was not changed by Sho‐saiko‐to [12] . Thus, we focused on the absorption processes of the drug in the small intestine.…”
Section: Introductionmentioning
confidence: 99%